THE INFLUENCE OF BRAND IMAGE ON CONSUMER SATISFACTION WITH PURCHASING DECISIONS AS INTERVENING VARIABLES (Case Study on Students of STIE Bina Karya Kota Tebing Tinggi) - Benhart Nainggolan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This study aims to determine " The Influence of Brand Image on Consumer Satisfaction with Purchasing Decisions as Intervening Variables (Case Study on Students of STIE Bina Karya Kota Tebing Tinggi)". The method of determining the sample used in this study is to use a saturated sampling technique of 57 samples which are students of STIE Bina Karya Kota Tebing Tinggi users of Honda Scoppy. Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Brand Image variable (X) affects the Purchase Decision variable (Z). Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is accepted, meaning that the Brand Image variable (X) has no effect on the Consumer Satisfaction variable (Y). Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is accepted, meaning that the Purchase Decision variable (Z) has an effect on the Consumer Satisfaction variable (Y). Based on the results of the analysis of hypothesis 4, it shows that the indirect effect of Brand Image (X) on Consumer Satisfaction (Y) through Purchase Decision (Z) is accepted rather than the direct influence of Brand Image (X) on Consumer Satisfaction (Y).